2019
DOI: 10.5334/tohm.457
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Quality of Randomized Controlled Trials in Restless Legs Syndrome Based on the CONSORT Statement

Abstract: Background: Randomized controlled trials (RCTs) are the cornerstone of modern medical research, and their reporting may not always be optimal. The Consolidated Standards of Reporting Trials (CONSORT) statement is an evidence-based means to improve the quality of RCTs' reporting by providing a checklist of recommended items. The aim of this study was to assess the reporting quality of published RCTs on the restless legs syndrome (RLS), based on a checklist arising from the CONSORT statement. Methods: Medical el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…Although the CONSORT statement does not specify what percentage of reported items should be considered adequate reporting, we defined adequate reporting using the definition used in previous studies [ 20 , 21 ]. We considered reporting to be adequate in each trial if the trial reported at least 75% of the items on the CONSORT 2010 checklist applicable to the trial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the CONSORT statement does not specify what percentage of reported items should be considered adequate reporting, we defined adequate reporting using the definition used in previous studies [ 20 , 21 ]. We considered reporting to be adequate in each trial if the trial reported at least 75% of the items on the CONSORT 2010 checklist applicable to the trial.…”
Section: Methodsmentioning
confidence: 99%
“…The number of articles that would have adequate reporting of the CONSORT items was used for sample size estimation. Assuming that 57% of the studies would have adequate reporting based on a previous study [ 21 ], according to a priori sample size determination, a sample size of 105 was required to get a precision of ±10% and a sample size of 128 would give precision of ±9%. In our study, we obtained a sample of 124 studies.…”
Section: Methodsmentioning
confidence: 99%
“…2018, Rikos et al . 2019). Similarly, an evaluation of randomized clinical trials across several Dental specialties highlighted multiple reporting inadequacies and recommended that this was a priority area for improvement (Saltaji et al .…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, randomized, sham-controlled studies must be preferred, and it is imperative that clinical trials in the future are of high quality, in order to provide solid evidence for the efficacy of rTMS. Finally, as has been shown, several published trials in various disorders are of suboptimal quality [82,83], a fact that limits the applicability of their results. Indeed, several of the aforementioned studies had several vital parts of their methodology inadequately reported.…”
Section: Discussionmentioning
confidence: 99%